Perancangan User Interface Menggunakan Metode Design Thinking Sistem Informasi Absensi Penggajian (Siap) Pada PT. Martimbang Jaya Utama - Aryani, Desi; Ruliansyah (CV. Ulil Albab Corp, 2025)
One of the things that must be considered is the management of company data. Including employee attendance and payroll data.The process of calculating employee salaries at PT. Martimbang Jaya Utama is still done manually and using separate spreadsheets. This manual process causes several problems, such as human error, delays in salary calculations, and issues in storing and managing attendance data. PT. Martimbang Jaya Utama urgently needs the digitalization of the payroll and attendance processes. The entire process of attendance recording and salary calculation can be done automatically and integrated with a web-based payroll attendance information system. This system allows access to organized historical data, which can facilitate the company in monitoring employee performance and improving operational efficiency. The system development method used is Design Thinking because this method supports the initial stage of system design according to needs. The final result of this research is the design of the User Interface for the attendance and payroll information system, which is expected to improve efficiency, accuracy, and transparency in employee data management. The design of this system can be used as a reference by the company, as it will facilitate the admin in managing attendance data and employee salary calculations, as well as help management make more accurate and faster decisions.